PROPHET MUHAMMAD’S BUSINESS ETHICS AS A REFLECTION OF SUCCESSFUL MUSLIM ENTREPRENEURS TOWARDS GOLDEN INDONESIA 2045 - Amalia, Tiara; Suleman, Muh. Asharif; Irwansyah, Moh; Nurmawati, Fulusia (Jurnal Syarikah : Jurnal Ekonomi Islam, 2024)
The Prophet’s business ethics must be used as a concrete rule for business people. But in reality, not a few online or offline business people violate ethics in doing sharia business, resulting in difficulties in realizing blessed and successful business practices towards golden Indonesia 2045. The purpose of this study is to explore the business ethics of the Prophet Muhammad Saw. as a role model in presenting superior and successful business people in the future. Researchers used a qualitative method with a field research approach. Researchers conducted observations, interviews, and documentation as an effort to collect data. The results of the findings in the study, namely; First, ethics in the Prophet’s business is fundamental in realizing the goals of a successful and blessed business, business practices run by every Muslim preneur require good ethical values, because without ethical elements in business will damage the economic order of business to society. Second, the Prophet Muhammad Saw is a figure who has business ethics principles that can be used as a reflection in current business activities, there are several noble values in the Prophet Muhammad Saw that must be owned by business people, including honesty, trustworthiness and responsibility, selling quality products, clean from usury practices, not hoarding goods. Third, the figure of a famous preacher from Medan is able to establish a divine business based on the ethics of the Prophet Muhammad Saw. in realizing a successful and blessed business.